To determine the value of \( h \) for which the equation \(-8 (x + 3) = h ( -x + 10)\) has zero solutions, we can analyze the equation step by step.
-
Distribute the terms:
- Left side: \(-8 (x + 3) = -8x - 24\)
- Right side: \(h ( -x + 10) = -hx + 10h\)
-
Rewrite the equation: \[ -8x - 24 = -hx + 10h \]
-
Rearranging: Rearranging the equation gives: \[ -8x + hx = 10h + 24 \] \[ (h - 8)x = 10h + 24 \]
For the equation to have zero solutions, we want the coefficient of \(x\) to be zero. This means:
- The term \((h - 8)\) should equal zero: \[ h - 8 = 0 \implies h = 8 \]
At the same time, the constant term on the right-hand side must not equal zero:
- The equation then is: \[ 10h + 24 \neq 0 \] Substituting \(h = 8\): \[ 10(8) + 24 = 80 + 24 = 104 \neq 0 \]
Thus, the complete sentence would be:
This equation will have zero solutions when \(h = 8\) because you get zero solutions when you have one number of \(x\) on either side of the equation and a non-zero equation for the constants.